2016
DOI: 10.1016/j.foreco.2015.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Tamm Review: Observed and projected climate change impacts on Russia’s forests and its carbon balance

Abstract: a b s t r a c tRussia's boreal forests provide numerous important ecosystem functions and services, but they are being increasingly affected by climate change. This review presents an overview of observed and potential future climate change impacts on those forests with an emphasis on their aggregate carbon balance and processes driving changes therein. We summarize recent findings highlighting that radiation increases, temperature-driven longer growing seasons and increasing atmospheric CO 2 concentrations ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 113 publications
(173 reference statements)
4
73
2
1
Order By: Relevance
“…As the frequency and severity of drought is expected to increase under a warmer and drier climate, elevated chances of postfire water stress may have a significant influence on ecosystem composition and function20. Recent climate warming has resulted in a rather uniform trend toward higher plant productivity and forest cover gain in the North, and a trend toward decreased productivity and forest cover loss in southern Siberian boreal forests66, similar to observations from Canada’s boreal forests70.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…As the frequency and severity of drought is expected to increase under a warmer and drier climate, elevated chances of postfire water stress may have a significant influence on ecosystem composition and function20. Recent climate warming has resulted in a rather uniform trend toward higher plant productivity and forest cover gain in the North, and a trend toward decreased productivity and forest cover loss in southern Siberian boreal forests66, similar to observations from Canada’s boreal forests70.…”
Section: Discussionmentioning
confidence: 55%
“…This analysis thus revealed that postfire recovery in boreal Larch forests of Northeastern China was collectively controlled by processes that controlled seed availability, site condition, and climate variability after fire. Anticipated increases in fire severity and moisture stress66, interacting with gradients of environmental conditions, will have significant influences on vegetation structure and function, and forest feedbacks to climate6768.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements taken at the stand level on different tree species in other regions have already detected a positive effect of warming and elevated atmospheric [CO 2 ] on forest productivity (Bosela et al., ; Charru et al., ; Schaphoff et al., ), but in areas where droughts have increased, forest productivity has decreased, despite increased temperature and atmospheric [CO 2 ] (Bonal, Burban, Stahl, Wagner, & Hérault, ; Sun et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the current century, this ecosystem is expected to undergo one of the largest increases in temperatures (3). Low mean annual temperatures (MATs) are a major constraint on boreal forest productivity, and increases in temperature and growing season length in recent decades are reported to have benefited tree growth over large areas of Fennoscandia (4) and Russia (5). In central and western areas of North American boreal forests, however, anal-ysis of recent tree-ring width data (6,7), in combination with stable carbon isotope analysis (8,9) and satellite images (10), suggests that changes in soil water balance have canceled potential gains in forest growth from recent warming.…”
Section: Forest Ecologymentioning
confidence: 99%